Numerical Simulation of the Inlet/Outlet Pressure Ratio Effect on the Heat Transfer Coefficient in an Air Turbine Cascade - He, Z.; Lin, J.H.; Sun, X.Y.; Gu, X. (Проблемы прочности, 2019)
Based on the state-of-the art methods of gas turbine cascade heat transfer assessment, a theoretical model of the two-dimensional air turbine cascade is proposed, wherein gas flows past the turbine blade profile. The velocity, temperature, and pressure fields, as well as the heat transfer distribution along the pressure and suction surfaces, the leading and trailing edges of the turbine blade were computed via FLUENT software at different pressure ratios. This permitted of studying the heat transfer evolution at different pressure ratios in the same position and at the same pressure ratio in different positions.